Comparative analysis of corolla tube development across three closely related Mimulus species with different pollination syndromes. Issue 3 (7th January 2021) - Gurung, Vandana; Yuan, Yao‐Wu; Diggle, Pamela K.
Abstract: Fusion of petals to form a corolla tube is considered a key innovation contributing to the diversification of many flowering plant lineages. Corolla tube length often varies dramatically among species and is a major determinant of pollinator preference. However, our understanding of the developmental dynamics underlying corolla tube length variation is very limited. Here we examined corolla tube growth in the Mimulus lewisii species complex, an emerging model system for studying the developmental genetics and evo‐devo of pollinator‐associated floral traits. We compared developmental and cellular processes associated with corolla tube length variation among the bee‐pollinated M. lewisii, the hummingbird‐pollinated Mimulus   verbenaceus, and the self‐pollinated Mimulus parishii . We found that in all three species, cell size is non‐uniformly distributed along the mature tube, with the longest cells just distal to the stamen insertion site. Differences in corolla tube length among the three species are not associated with processes of organogenesis or early development but are associated with variation in multiple processes occurring later in development, including the location and duration of cell division and cell elongation. The tube growth curves of the small‐flowered M. parishii and large‐flowered M. lewisii are essentially indistinguishable, except that M. parishii tubes stop growing earlier at a smaller size, suggesting a critical role of heterochrony in the shift from outcrossing to selfing. These results not only highlight the developmental process associated with corolla tube variation among species but also provide a baseline reference for future developmental genetic analyses of mutants or transgenic plants with altered corolla tube morphology in this emerging model system. Abstract : Research Highlights: Changes in rate and duration of corolla tube growth are associated with the evolution of divergent floral morphology. Both cell division and elongation are associated with changes in corolla tube growth. Elongation is most pronounced in the region distal to stamen insertion and occurs very late in development.